SAT0650 [18F]FLUORO-PEG-FOLATE pet: a novel imaging technique to visualize rheumatoid arthritis. (15th June 2017) - Verweij, N; Bruijnen, S; Gent, Y; Huisman, M; Jansen, G; Molthoff, C; Chen, Q; Low, P; Windhorst, A; Lammertsma, A; Hoekstra, O; Voskuyl, A; et al.
Abstract : Background: Imaging arthritis activity in rheumatoid arthritis (RA) patients using PET macrophage tracers holds promise for both early diagnostics and monitoring response to therapy (1, 2). Previously, ( R )-[ 11 C]PK11195 has been used, but this macrophage tracer is limited due to high background uptake, especially in bone and bone marrow. Recently, a novel macrophage tracer, [ 18 F]fluoro-PEG-folate, was developed, which showed excellent targeting of the folate receptor beta on activated macrophages in synovial tissue in a preclinical arthritic rat model (3). Objectives: To assess the value of [ 18 F]fluoro-PEG-folate PET-CT for imaging inflamed joints in patients with clinically active RA. Methods: Nine RA patients with at least two clinically inflamed hand joints were included. PET-CT scans of the hands were acquired after intravenous administration of either 185 MBq of [ 18 F]fluoro-PEG-folate (n=6) or 425 MBq of ( R )-[ 11 C]PK11195 (n=3). Volumes of Interest (VOI) were drawn over joints with visually marked uptake and Standardized Uptake Values (SUVs) were calculated. Background VOIs were drawn on metacarpal bone in order to calculate Target-to-Background (T/B) ratios. Results: No side effects were observed, establishing the safety of [ 18 F]fluoro-PEG-folate for use in humans. [ 18 F]fluoro-PEG-folate clearly showed uptake in arthritic joints, as shown in Figure 1 . In patients scanned with [ 18 F]fluoro-PEG-folate, 25 positive joints were seen, with a minimum of two joints per patient. Clinical arthritis was confirmed in 10 of these 25 joints, and was absent in 15 positive joints, suggesting the presence of subclinical inflammation. Whilst both [ 18 F]fluoro-PEG-folate and ( R )-[ 11 C]PK11195 accumulated in arthritic joints, [ 18 F]fluoro-PEG-folate showed a significantly lower background uptake than ( R )-[ 11 C]PK11195 (SUV of 0.18 vs 0.75; p<0.001) respectively. T/B-ratios were significantly higher for [ 18 F]fluoro-PEG-folate (3.60vs 1.72, p=0.009). Conclusions: This first in patient study clearly demonstrates the potential of [ 18 F]fluoro-PEG-folate PET-CT as macrophage tracer to image both clinically and sub-clinically affected joints in RA patients. [ 18 F]fluoro-PEG-folate showed better characteristics for arthritis imaging than the established tracer ( R )-[ 11 C]PK11195 because of its lower background signal. References: Gent YY, et al. J Rheumatology. 2014; 41: 2145–52. Gent YY, et al. Arthritis Rheum. 2012; 64: 62–6. Gent YY, et al. Arthritis Res Ther. 2013; 15: R37. Disclosure of Interest: None declared